DISTANCE EDUCATION TECHNOLOGIES AND THEIR IMPLEMENTATION IN THE TRAINING SYSTEM - Gulhayo Saidjon qizi Rahmonova (Scholar Express Journal, 2023)
In this article, the concepts of distance education and distance education are covered in terms of content and their differences are explained. The need to apply distance education technologies to the process of qualification improvement is presented. The establishment and implementation of the distance training system for teachers in our republic has been analyzed step by step
Keywords: distance education; development of pedagogue; system of distance professional development of teachers